Investigation of cell aggregation on the substrate of a parallel-plate flow chamber - Bai, F; Dong, C; Cao, C; Sun, R (Cellular and Molecular Biology, 2015)
Adhesion of tumor cells (TCs) to polymorphonuclear neutrophils (PMNs) tethered on a monolayer of vascular endothelial cells (ECs) in shear flows is investigated theoretically. Both TC-PMN and PMN-EC aggregations are modeled using the population balance equations (PBEs). Parameters in the model obtained by curve fitting show that an increase of shear rate or viscosity will suppress the formation of aggregates and promote the breakage of them. Analysis on the collision frequency suggests that the averaged encounter duration is affected by viscosity. Based on the model, a nonlinear connection between the number of migrated TCs and the concentration of PMNs in the flow near the substrate is presented.